Cu-catalyzed mild and efficient oxidation of THβCs using air: application in practical total syntheses of perlolyrine and flazin. Issue 13 (12th February 2018) - Zheng, Bo; Trieu, Tien Ha; Meng, Tian-Zhuo; Lu, Xia; Dong, Jing; Zhang, Qiang; Shi, Xiao-Xin
Abstract : A mild, efficient and ecofriendly method for synthesis of β-carbolines via Cu-catalyzed aerobic oxidation of 1, 2, 3, 4-tetrahydro-β-carbolines (THβCs) was developed. In addition, this method was successfully applied in the practical total syntheses of perlolyrine and flazin. Abstract : A mild, efficient and environmentally benign method for synthesis of aromatic β-carbolines via Cu(ii )-catalyzed oxidation of 1, 2, 3, 4-tetrahydro-β-carbolines (THβCs) was developed, in which air (O2 ) was used as the clean oxidant. This method has advantages such as environmentally friendliness, mildness, very good tolerance of functional groups, high yielding and easy experiment operation. In addition, this new methodology was successfully applied in the efficient and practical total syntheses of β-carboline alkaloids perlolyrine and flazin.